GERMANA ERNST INTERPRETE DI GIROLAMO CARDANO - GUIDO GIGLIONI (Lexicon Philosophicum)
Germana Ernst, an international authority on Tommaso Campanella’sphilosophy, was also a fine interpreter of Girolamo Cardano, whose work she investigatedin many of its wide-ranging dimensions. The figure who emerges from Ernst’s analysis isan open-minded explorer of natural marvels and human foibles. Ernst has written seminalstudies on topics related to Cardano’s work in the areas of astrology, witchcraft andautobiography. It is especially with respect to his autobiographical account that Ernst hasgiven us illuminating pages on the most troubling aspects of Cardano’s life: the death ofhis firstborn son, his imprisonment and his unsettling experiences of mental pain.